Force Majeure, Impossibility, Frustration & the Like: Excuses for Non-Performance; the Historical Origins and Development of an Autonomous Commercial Norm in the CISG - Peter Mazzacano (Nordic Journal of Commercial Law, 2011)
This article considers the extent to which a problematic legal doctrine is an autonomous1 international commercial norm, and capable of relative uniformity within the context of the 1980 United Nations Convention on Contracts for the International Sale of Goods (“CISG” or “Convention”)2 and its goal for a sales law that is transnational in design. This norm, is commonly known as force majeure, an Act of God, impossibility, frustration, the German wegfall der geschaftsgrundlage, the French imprevision, and the like, but embodied in CISG Article 79 under the neutral wording of “failure to perform…due to an impediment beyond his control” in CISG. A premise to be explored is that while phrase “failure to perform…due to an impediment beyond his control” in CISG Article 79 may have developed out of an amalgamation of similar national conceptions which, in turn, grew from the conflicting Roman maxims pacta sunt servanda and rebus sic stantibus, Article 79’s excuse for non-performance ultimately stands alone as an autonomous international doctrine under the CISG in private international law. It belongs to a private legal order and is part of the non-state commercial lexicon of the new lex mercatoria. This development plays a crucial role for uniformity in private international law generally, and specifically for international sales law. It supports the idea that in certain cases, particularly in international commercial transactions, individual domestic legal doctrines and norms—some of which evolved out of Roman maxims— can transcend state-based law-making, and may ultimately coalesce into autonomous international principles, regardless of their distinctive development by way of positive law in state-based jurisdictions. Such a development also questions the role of the state in the creation of legal orders. This paper argues that this development of an autonomous legal principle—“failure to perform…due to an impediment beyond his control”—is part of the international commercial lingua franca. Further, this private law-making is also evidence of a growing autonomous global legal culture that is truly independent of any national sovereign. This development affects traditional (i.e. state-based) legal boundaries. The implications for transnational law and global governance is that, in the absence of a supranational legislator, the participants themselves, the international merchants and bankers, are needed—indeed, required—to determine their own legal norms. There is, thus, a greater role for industry practices, custom, and party autonomy in the modern globalized environment.